2012
DOI: 10.3190/jgeosci.008
|View full text |Cite
|
Sign up to set email alerts
|

Subsolidus behavior of niobian rutile from the Písek region, Czech Republic: a model for exsolution in W- and Fe2+>>Fe3+-rich phases

Abstract: Niobian rutile with substantial W content is associated with black tourmaline, beryl, zircon, xenotime-(Y), monazite-(Ce), "písekite", and possibly pseudorutile or pseudobrookite in two cogenetic, beryl-columbite-subtype, granitic pegmatites at Písek and Údraž, southern Bohemia, Czech Republic. Crystals, up to 3×1 cm in size, consist of relics of a primary, phase-homogeneous but oscillatorilly zoned niobian rutile phase and of exsolution intergrowths of depleted niobian rutile with granular titanian-tungstenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
2
9
0
4
Order By: Relevance
“…Common W-bearing minerals in both granite-pegmatite systems open a potential use of W as an indicator of the mixed signature of a pegmatite. However, W is a typical trace to minor element in (Nb,Ta,Ti)-oxide minerals in both NYF (Škoda et al 2006(Škoda et al , Škoda & Novák 2007 and in LCT pegmatites (e.g., Novák & Černý 1998b, 2001, Černý et al 2007, Novák et al 2008 in the Moldanubian Zone. The Třebíč pluton and O'Grady Batholith represent granite-pegmatite systems with a similar origin of parental granite and geochemistry.…”
Section: Comparison Of the Kracovice Pegmatite With Similar Li-bearinmentioning
confidence: 97%
“…Common W-bearing minerals in both granite-pegmatite systems open a potential use of W as an indicator of the mixed signature of a pegmatite. However, W is a typical trace to minor element in (Nb,Ta,Ti)-oxide minerals in both NYF (Škoda et al 2006(Škoda et al , Škoda & Novák 2007 and in LCT pegmatites (e.g., Novák & Černý 1998b, 2001, Černý et al 2007, Novák et al 2008 in the Moldanubian Zone. The Třebíč pluton and O'Grady Batholith represent granite-pegmatite systems with a similar origin of parental granite and geochemistry.…”
Section: Comparison Of the Kracovice Pegmatite With Similar Li-bearinmentioning
confidence: 97%
“…Examples in the French Massif Central include the Ta-Sn-Li mineralization of the Beauvoir granite (Cuney et al 1992;Raimbault et al 1995), the columbite-tantalite minerals of the complex lepidolitesubtype pegmatites of Chèdeville (Raimbault 1998), as well as the cassiterite and wolframite-group minerals of the Vienne granite (Cuney et al 2002;Bouchot et al 2005). The rare-metal deposits linked to the LCT pegmatites occur also in the Bohemian Massif, Czech Republic (Johan and Johan 1994;Černý et al 2007;Breiter et al 2007) and the tin and tungsten deposits are known from the Cornwall Massif, south-eastern England (Charoy 1986;Willis-Richards and Jackson 1989). In the Iberian Massif, the pegmatite fields of Lalín-Forcarei (Fuertes-Fuentes and Martín-Izard 1998) and Fregeneda-Almendra (Roda-Robles 1993;Roda-Robles et al 2007;Vieira et al 2011) are some of the best-known rare-metal deposits associated with leucogranites in northern and western Spain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have indicated that Nb is highly compatible with rutile during magma crystallization (Brenan, Shaw, Phinney, & Ryerson, ; Linnen & Keppler, ). Here, Fe 2+ + 2(Nb, V) 5+ = 3Ti 4+ has been suggested as one of the main replacement mechanisms for the incorporation of Nb in rutile (Černý, Novak, Chapman, & Ferreira, ). The rutile in the Zhujiayuan deposit is common, such that most rutile deriving from magma genesis contains a certain amount of Nb 2 O 5 (0.75–1.79 wt%) (Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 99%